"There Is No Moral They Can Teach Us": Adolescents' Perspectives on School-Based Sexuality Education in a Semiurban, Southwestern District in Nigeria. Issue 3 (3rd July 2017) - Aham-Chiabuotu, Chidimma B.; Aja, Godwin N.
ABSTRACT: There is limited data on the implementation of Comprehensive Sexuality Education in Nigerian schools. This study explored In-School adolescents' perspectives on the implementation and utility of the Family Life and HIV/AIDS Education Curriculum, using questionnaires and focus group discussions. Findings reveal that sexuality education in schools is mostly moralistic and cognitive in emphasis, with limited adaptation of interactive methodologies. Inadequate teacher training, teachers' sexual double standards, and limiting curriculum to junior classes were identified as major setbacks. Curriculum expansion, Comprehensive School health programming, continuous teacher training and ensuring that teachers are held accountable for their behaviors are recommended.